Insect Diversity and Visitation Patterns on Nephelium ramboutan-ake in Mekarsari, Bogor - Junaidi, Muhamad; Chikmawati, Tatik; Atmowidi, Tri; Djuita, Nina Ratna (Jurnal Biodjati, 2025)
Information on flower-visiting insects, especially pollinators of the pulasan plant (Nephelium ramboutan-ake), a species that tends to cross-pollinate, is essential for increasing fruit production. Unfortunately, there is minimal information on flower-visiting insects associated with pulasan. This research aimed to study the diversity and abundance of visiting insects on pulasan in the Mekarsari Fruit Garden, Bogor. Observations of insects were conducted using the fixed sample method, with samples taken every 20 minutes through direct observation from 06:00 am to 02:00 pm during the flowering period. Results showed that 24 insect species, belonging to 24 genera across six orders, visited the pulasan, with the order Diptera being the most dominant among the visiting insects. The potential insect species as pollinators of pulasan were Lathyrophthalmus sp. and Amata huebneri. Knowledge about flower-visiting insects plays an important role in the conservation of insects—especially pollinators—as well as the pulasan plant, a local species.